Morphologycal and structural investigations of nanoporous aluminum - Dikhanbayev, K.K.; Akimhanov, O.T.; Baiganatova, Sh.B.; Nikulin, V.E.; Tairbaev, T.I. (Recent Contributions to Physics, 2012)
In this paper we consider the structure of nanoporous aluminum obtained by electrochemical etching in electrolyte containing an aqueous solution of oxalic acid. The morphology, kinetics of an anodic coating formation on aluminum plate are shown, chemical reactivity in the thermal stabilization is determined. We compared the results of measurements of the photoluminescence spectra of porous alumina.